PELATIHAN PEMBUATAN SURAT LAMARAN KERJA DAN KARTU NAMA SISWA MENGGUNAKAN MAIL MERGE DI MADRASAH ALIYAH SWASTA YPI BATANG KUIS - Ommi Alfina; Elida Tuti Siregar; Dwi Enda Agustia Hasugian (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
This community service activity is one of the Tri Dharma Perguruan Tinggi by providing learning to students at Madrasah Aliyah Swasta YPI Batang Kuis in training on making job applications and student business cards using Mail Merge. Mail Merge is a facility in Ms. Word that is used to deal with correspondence problems such as job application letters, invitation letters, sales promotion letters, business cards, and various other types of document creation, which can be sent to multiple recipients/destinations using the information stored in the list, database, or spreadsheet. The advantage of using mail merge is that it makes it easier for the letter/document maker because it only creates one type of letter/document that can be sent to several different recipients. Through this training, Madrasah Aliyah Swasta YPI Batang Kuis students are expected to be able to take advantage of the Mail Merge feature to make job application letters and student business cards more easily and more efficiently as a support in the teaching and learning process.